A STUDY ON CHALLENGES BEFORE UNITED NATIONS - Dr. Ashima Ghosh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
While declaring the objectives in the Charter of the United Nations, it has been made clear from the very beginning that the first goal is to liberate mankind from the horrors of war. Obviously, its most important effort is to make impossible the conditions that give rise to war and destroy peace. At the time of establishment, the memories of the Second World War were fresh and the struggle against colonialism was widespread throughout the world. In these circumstances, the reasons that made peace in danger were clearly identifiable